2017
DOI: 10.3390/ijms18030597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hsa_circ_0004277 as a New Biomarker for Acute Myeloid Leukemia via Circular RNA Profile and Bioinformatics Analysis

Abstract: Circular RNAs (circRNAs) represent a widespread class of non-coding RNAs, which drew little attention in the past. Recently, limited data showed their promising future to act as biomarkers in human cancer, but the characteristics and functions remain largely unknown in hematopoietic malignancies, especially in leukemia. In this study, with the help of circRNA microarray, we demonstrated the expression profile of circRNAs in acute myeloid leukemia (AML) patients, and identified a large number of circRNAs possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 27 publications
(34 reference statements)
2
123
0
1
Order By: Relevance
“…In this study, we demonstrated that circ-U2AF1 expression was upregulated in glioma tissues, relatively, to adjacent nontumorous tissues. The expression of hsa-mir-7-5p was downregulated, whereas Li et al, 2017;Lu et al, 2017;Meng et al, 2017). Here, we established that circ-U2AF1 might play an oncogene role in glioma.…”
Section: Discussionsupporting
confidence: 56%
“…In this study, we demonstrated that circ-U2AF1 expression was upregulated in glioma tissues, relatively, to adjacent nontumorous tissues. The expression of hsa-mir-7-5p was downregulated, whereas Li et al, 2017;Lu et al, 2017;Meng et al, 2017). Here, we established that circ-U2AF1 might play an oncogene role in glioma.…”
Section: Discussionsupporting
confidence: 56%
“…With the rapid progression and wide application of high-throughput sequencing and microarray, the expression pattern of circRNAs in various human diseases are increasingly reported, and the dysregulated expressions of circRNAs are shown to contribute to the pathogenesis of various cancers [7,[9][10][11][14][15][16][17][18][19]. For instance, in hepatitis B-related HCC, 189 upregulated circRNAs and 37 downregulated circRNAs were found by circRNA microarray, and circRNA_100,338 is further validated to be associated with metastatic progression by acting as an endogenous sponge for miR-141-3p [7].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of circRNA microarrays, our knowledge about circRNA expression patterns has been initially uncovered in various diseases. In cancer research, circRNA expression patterns have been studied in some solid tumors including breast cancer, esophageal squamous cell cancer, epithelial ovarian cancer, etc., and a number of circRNAs are disclosed to involve in the pathophysiological progression of these malignancies [8][9][10][11]. As for hematological malignancies, an extensive analysis of circRNA expression profiles reveals a total of 464 dysregulated circRNAs (147 upregulated and 317 downregulated) in acute myeloid leukemia (AML) patients compared with healthy controls, and among these circRNAs, circ_0004277 is validated to be positively associated with prognosis in AML patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed circRNAs with statistical significance were identified through fold change filtering or volcano plot filtering. Hierarchical clustering was performed to show the distinguishable circRNA expression pattern among different samples [10, 11]. Circular RNAs exhibiting fold change>2 and P -value<0.05 were selected as significantly differentially expressed circRNAs.…”
Section: Methodsmentioning
confidence: 99%